The adolescent athlete: A developmental approach to injury risk - McKay, D.; Broderick, C.; Steinbeck, K. (Pediatric Exercise Science, 2016)
The prevention and management of sports related injury during adolescence remains an important priority for all involved in adolescent sport. Injury risk increases throughout adolescence, with an association with both increasing age and pubertal development. Although the influence of the gonadal hormones and growth factors are intrinsically linked to specific physical and physiological changes of puberty, little empirical evidence exists to confirm a causal relationship between the hormonal changes of puberty and a quantifiable change in injury risk. Physical development in adolescents precedes cognitive development, with physical development predominant in early to mid-adolescence whereas adolescent brain development including changes in brain structure and cognition, not complete until the third decade. We have proposed mechanisms whereby the physical and cognitive changes of normal puberty and their temporal relationship may temporarily increase the risk of musculoskeletal and concussive head injury, and influence the development of conditions such as Overtraining Syndrome relevant to adolescent athletes. Further research is needed to evaluate the association between injury risk and physical and cognitive development. Maintaining a balance between the higher training burdens associated with early sport specialization and talent identification programs, and injury risk can assist in safeguarding the wellbeing of the developing adolescent athlete. Strategies such as periodization and load monitoring should be used in combination with an understanding of the developmental changes of adolescence, as well as an assessment of the physical and neurocognitive maturity of the individual athlete. The risk of not appropriately balancing the competing priorities of youth athlete development and injury risk and its potential consequences may result in both a lost opportunity in the development of a young athlete as well as a lost opportunity to optimize future health outcomes of the adolescent.